Survey on awareness of rabies as zoonotic disease among dog owners in University Veterinary Hospital (UVH), Faculty of Veterinary Medicine, Universiti Putra Malaysia - Abu Bakar, Amirah (2018)
Rabies is regarded as one of the most important zoonotic diseases as all mammals are susceptible to rabies including human. It is especially important for dog owners to be aware of rabies to prevent disease transmission when handling the infected animals. This study was conducted to determine the level of awareness of rabies as zoonotic disease among dog owners in University Veterinary Hospital (UVH). Questionnaire consist of multiple choice and closed-endedquestions comprising the different level of responsiveness on rabies was prepared and distributed to different dog owners at UVH for three weeks. A total of 33 respondents participated in this project. The data was analyzed using descriptive statistics to determine the level of awareness of Rabies. About 85% (n=28) of dog owners showed low level of awareness. The level of awareness and the source of information on rabies were significantly associated [P value = 0.036 (α = 0.05)]. In addition, nine out of twelve dog owners (75%) who experienced dog bite or dog scratch did not seek medical treatment. Thus, we can conclude that the level of awareness of rabies as zoonotic disease among dog owners was at low level despite knowing it is infectious to human.